SREBF1, a target gene of multiple sclerosis and coronary heart disease: based on mendelian randomization study - Linqin Du; Yangyang Cui; Yang Zhou; Ofe Eugene Kwaku; Xuefeng Ding; Lang Zeng; Shikang Li; Lijuan Xiong; Yonghong Zhang; Peng Zhou; Kun Wang; Rongchuan Yue (Hereditas)
Abstract Background and purpose Research shows that people with multiple sclerosis (MS) are more likely to experience cardiovascular complications. However, the precise mechanisms underlying this association remain unclear. This study investigated the causal relationship between MS and coronary heart disease (CHD) using Mendelian randomization (MR) techniques to clarify direct effects and identify relevant target genes. Methods We conducted various methods, including two-sample MR. method, reverse, and multivariable MR analyses, to examine the causal relationship between MS and CHD. These. methodologies effectively mitigate confounding variables and neutralize adverse causal effects. Additionally, the study explored the involvement of social factors through a two-step MR analysis. The research team performed a thorough screening of differentially expressed genes in MS based on GEO database, identifying potential target genes that may be associated with genetic risk of CHD. Enrichment analyses and protein-protein interaction studies were used to elucidate biological functions associated with these genes. We included colocalization analysis and summary data-based Mendelian randomization (SMR) method for further screening of core genes to obtain target genes.Finally, we investigated how these genes might affect health by conducting a phenome-wide MR analysis. Results Our findings revealed that genetic predisposition to MS significantly increases the risk of CHD, with an IVW-MR analysis yielding an odds ratio of 1.091 (95% CI: 1.030, 1.155, P = 0.0029). Mediation analysis revealed that frailty mediated 20.2% of the effect of MS on CHD (P = 0.026), suggesting that frailty is a critical pathway in this relationship. Additionally, low-density lipoprotein (LDL) is associated with an increased risk of developing both MS and CHD. We identified 3025 differentially expressed genes and 130 genes causally linked to CHD. Protein-protein interaction network analysis identified 77 interacting genes, with core genes such as SREBF1 involved in organelle regulation and nucleic acid metabolism. Colocalization analysis further supported the presence of shared genetic variants between IL6R and SREBF1 associated with CHD, with posterior probabilities (PPH4) of 90.2% and 92.3%, respectively. Interestingly, summary mendelian randomization (SMR) analysis revealed that SREBF1 may be a target gene for MS(bSMR=-0.174,PSMR = 0.0218, PHEIDI = 0.2806, topSNP: rs12951376). Further analysis of the phenome-wide MR did not find significant evidence of side effect associated with targeted therapy against SREBF1. Conclusion This study provided genetic evidence indicating that indivduals with MS face higher risk of coronary heart disease. Furthermore, SREBF1 maybe a critical target gene which would significantly contribute to drug development.